A single nucleotide polymorphism produces different transcription profiles in Campylobacter jejuni’s cysM - Gunther IV, Nereus W.; Kanrar, Siddhartha; Abdul-Wakeel, Aisha; McAnulty, Michael J.; Renye, John; Uknalis, Joseph; Uhlich, Gaylen A. (Frontiers in Microbiology, 2025)
A single nucleotide polymorphism (SNP) in the 126 bp untranslated region (UTR) directly upstream of Campylobacter jejuni’s cysM (cysteine synthase) results in significant effects on gene transcription. UTR sequences, containing the predicted promoter region of cysM, from 264 different strains were compared, and revealed a SNP twenty nucleotides upstream of the cysM translation start site. In 219 strains the UTR sequence contained a guanine at this locus, and the remaining 45 strains had an adenine at the same position. Strains possessing the guanine SNP showed higher amounts of cysM transcripts compared to adenine SNP strains. When both UTR regions were cloned upstream of the major flagellar subunit (flaA) the guanine SNP UTR resulted in significantly greater levels of flaA transcription compared to the adenine SNP containing UTR. Additionally, when the UTR containing the guanine SNP was fused to flaA, motility was restored for a flaAB null mutant. Motility was not rescued initially when flaA was fused to the UTR containing the adenine SNP UTR. However, when the flaAB null mutant, containing a copy of flaA fused to the adenine-containing UTR, was incubated in Brucella broth for a minimum of two consecutive passages each lasting 48 h, transcription of flaA increased and motility was restored. Additional analysis of the flaA mRNA produced by the strain containing the adenine SNP UTR fused to flaA grown in Brucella broth versus agar suggests that the effects on motility occurred through blocking of full-length mRNA production.